2022
DOI: 10.1021/acs.chemrestox.2c00058
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic INS-1 β-Cell Response to Thapsigargin and Rotenone: A Comparative Proteomics Analysis Uncovers Key Pathways of β-Cell Dysfunction

Abstract: Insulin-secreting β-cells in the pancreatic islets are exposed to various endogenous and exogenous stressing conditions, which may lead to β-cell dysfunction or apoptosis and ultimately to diabetes mellitus. However, the detailed molecular mechanisms underlying β-cell’s inability to survive under severe stresses remain to be explored. This study used two common chemical stressors, thapsigargin and rotenone, to induce endoplasmic reticulum (ER) and mitochondria stress in a rat insuloma INS-1 832/13 β-cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…On the other hand, L13a-mediated translational silencing of ceruloplasmin expression was among the dysregulated pathways induced by both stressors (Rot and ThaGlc). This observation was also consistent with our recent reports in rotenone-treated INS-1 cells [16]. Many of these associated proteins relating to RNA binding that contribute to structural integrity of ribosomes were reduced in these stress responses, reflecting the acute conditions leading to accumulation of misfolded proteins in ER.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, L13a-mediated translational silencing of ceruloplasmin expression was among the dysregulated pathways induced by both stressors (Rot and ThaGlc). This observation was also consistent with our recent reports in rotenone-treated INS-1 cells [16]. Many of these associated proteins relating to RNA binding that contribute to structural integrity of ribosomes were reduced in these stress responses, reflecting the acute conditions leading to accumulation of misfolded proteins in ER.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our previous observations in INS-1 cells [16], we also found that OXPHOS proteins dysregulated by both rotenone and the combined ThaGlc in human islets. Despite recent studies demonstrated the critical regulatory link between oxidative protein folding in ER and mitochondrial dysfunction through OXPHOS, the molecular mechanism of how these oxidative stresses interact in variety of disease progression is still elusive.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To determine if VK and γ-carboxylation can protect β-cells from the acute effects of ER stress, INS-1 832/3 β-cells were cultured for 24h in media containing 25mM glucose in the presence or absence of thapsigargin, an inhibitor of the sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), and a pharmacological inducer of ER stress (Sharma et al, 2015). Doses of thapsigargin (10-40nM) inducing moderate to elevated cell death in INS-1 cell cultures were selected based on previously published data (Weldemariam et al, 2022). Induction of Grp78/BiP and phospho(Ser724)-IRE following thapsigargin treatment confirmed the presence of ER stress and UPR (Fig.…”
Section: Vitamin K Attenuates Apoptosis Induced By Er Calcium Depletionmentioning
confidence: 99%